1997
DOI: 10.1038/sj.sc.3100407
|View full text |Cite
|
Sign up to set email alerts
|

The surgical treatment of acute spinal paralysed patients

Abstract: Following the basic principles of Sir Ludwig Guttmann in respect of the comprehensive care and management of spinal cord injured patients, the German SCI centers try to admit those freshly injured preferably on the first day of onset, providing spinal surgery and intensive care. In our series of recent comprehensive spinal paralysed patients admitted from Jan 1st 1993 to Dec 31st 1995 178 patients requested operative decompression and stabilization out of a total of 255 patients. 51.4% of the patients had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…The only therapeutic window established in humans, actually, is the 8-h trauma-to-treatment window reported in the NASCIS-2 in which methyl-prednisolone was used. [11][12][13] The limit of 24 h has been used in this study for two practical reasons: (1) very few reports provide data on an earlier treatment; (2) less than 50% of patients can be currently admitted to spinal cord centres within 24 h. 57,58 Analysis of results and limitations of the study The meta-analytic procedure consisted of extraction, pooling and statistical analysis of data from parent studies. Since only one prospective randomized (Class I evidence) 39 and eight prospective nonrandomized case series (Class II evidence) 32,34,40,[41][42][43][44][45] were found from the literature search, the meta-analysis was based on studies reported on retrospective case series with historical controls (Class III evidence).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The only therapeutic window established in humans, actually, is the 8-h trauma-to-treatment window reported in the NASCIS-2 in which methyl-prednisolone was used. [11][12][13] The limit of 24 h has been used in this study for two practical reasons: (1) very few reports provide data on an earlier treatment; (2) less than 50% of patients can be currently admitted to spinal cord centres within 24 h. 57,58 Analysis of results and limitations of the study The meta-analytic procedure consisted of extraction, pooling and statistical analysis of data from parent studies. Since only one prospective randomized (Class I evidence) 39 and eight prospective nonrandomized case series (Class II evidence) 32,34,40,[41][42][43][44][45] were found from the literature search, the meta-analysis was based on studies reported on retrospective case series with historical controls (Class III evidence).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The advances in spinal stabilization in the last two decades have provided better stability of the bony architecture, hence preventing further instability. 10,11 There is also controversy about early mobilization of the cervical spine injured group. Early mobilization in this group was thought to have worse outcomes on the neurology.…”
Section: Introductionmentioning
confidence: 99%
“…11 In the presence of complete paralysis before the operation, surgical treatment does not produce any essential improvement apart from pain relief, however, neurological improvement tends to be provided by immediate decompression in case of paresis. 12,13 Accordingly, in our case, the patient showed improvement of neurological deficits, although he underwent operation 1 week after the onset of paresis. Thus, these results confirm that early diagnosis is important for better neurological improvement in patients with paresis caused by tumor-related spinal cord compression.…”
Section: Discussionmentioning
confidence: 52%